Research Trends on Patient Satisfaction during the Pandemic - Nuryakin (Universitas Muhammadiyah Yogyakarta, 2023)
The COVID-19 pandemic has affected the health sector, including mental health, and is considered a global pandemic that contributed to research in the health sector. This study aims to study research trends on patient satisfaction during a pandemic. A bibliometric analysis helped to measure research trends on patient satisfaction during a pandemic. The research approach elaborated data in the bibliography through extraction from the Scopus database, then filtering research articles published during 2019-2021 using bibliometric techniques, co-citation analysis and citation analysis. This study used bibliometric analysis by conducting a library search paper referring to Scopus databases. Scopus database identified relevant articles published from 2019 to 2021 using VosViewer. The results showed research trends conducted in-depth patient satisfaction studies over the past three years. The trend of publications on patient satisfaction continued to increase (2020 –2022). However, in 2021 – 2022, it was decreasing. International Journal of Environmental Research and Public Health published many papers on patient satisfaction. Loughborough University was the institution with the most publications. Research field citations on patient satisfaction showed Biasco, G. with the most citations.